Al-Firqah an-Najiyah dalam Pandangan Hadis: Studi Takhrij dan Syarah - Yuda Rismawan; Deni Miharja; Husnul Qodim (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about firqah najiya. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about firqah najiya in the history of Abu Daud no. 3981. The results and discussion of this study indicate that the quality of the hadith is considered authentic with the qualifications of maqbul ma'mul bih as evidence for practicing Islam. This study concludes that the hadith narrated by Abu Daud no. 3981 is relevant to be used to strengthen aqidah and strengthen the integrity of Muslims within the scope of al-jama'ah.